'I have heard of the end of writing': Kristjana Gunnars and Roland Barthes. Issue 1 (March 2018) - Gardner, Calum
Abstract : The work of Icelandic-Canadian writer Kristjana Gunnars crosses genres and confuses the boundaries between fiction, poetry, biography, essay, and theory. This article addresses her relationship to the French literary theorist Roland Barthes. By paying close attention to the texts which mention Barthes specifically, the poem-cycle Carnival of Longing (1989) and the memoir Zero Hour (1991), it is possible to examine the approaches to desire, grief, and writing that give both Gunnars's and Barthes's work their enduring relevance. Gunnars reads Barthes against the grain, seeing the fragmentary strategy of A Lover's Discourse (1979) as a refusal of genre and taking Writing Degree Zero 's (1968) revolutionary strategy of 'colourless writing' as a strategy for dealing with grief. An examination of her citations of and allusions to Barthes will show us how Gunnars interprets and remakes theory into poetry.